ENGLISH TO INDONESIAN TRANSLATION TECHNIQUE IN CRUELLA MOVIE - Zulita, Selma; Theresia Cicik Sophia Budiman; Ajeng Setyorini (UIN Raden Mas Said Surakarta, 2025)
This study examines the translation techniques used in the Indonesian subtitles of Cruella (2021) by applying Molina and Albir’s (2002) framework and House’s (2015) Translation Quality Assessment (TQA). The objectives are to identify the techniques, determine the dominant one, and analyze its impact on meaning, tone, and character portrayal. Using a descriptive qualitative method, a total of 150 data were analyzed, revealing seven techniques: Literal Translation (46.67%), Modulation (36.00%), Transposition (7.33%), Reduction (7.33%), Adaptation (6.00%), Amplification (4.00%), and Equivalence (0.67%), with Literal Translation as the most dominant. The TQA results show that while literal translation successfully maintains ideational meaning, it often causes shifts in interpersonal function (tone and emotional nuance) and affects textual function, particularly humor and stylistic portrayal. These findings highlight both the strength and limitation of literal translation in balancing semantic accuracy with stylistic and cultural nuances in film subtitling.